Design of Emergency Position Reporting System for Disasters Using Amateur Radio and Automatic Packet Reporting System (APRS) as a Mobile Station Operator for Educational Purposes - Sok Oeun Un; Kimtho Po; Kosorl Thourn; Rathna Pec; Channareth Srun; Seven Siren (Universitas Pendidikan Indonesia (UPI), 2023)
The emergency position reporting system is proposed for disasters using amateur radio and Automatic Packet Reporting System (APRS) as mobile station operators for unexpected natural disasters after the Internet and mobile communication system infrastructure are destroyed surrounding the disaster areas. The location tracking systems are used with amateur radio devices and implemented with APRS in the act of position reports. The position information is received from the smartphone’s Global Positioning System (GPS) using the offline mode to the APRS via Bluetooth network that is connected to transceivers. The transceiver used the dual-band Yagi antenna 145Mhz/435Mhz called Mobile Station Operator (MSO) as the APRS client using callsign. The MSO collected the location data sent to the Response Station Operator (RSO) that combined with APRS, transceivers, and antenna. The server system allowed data location information monitoring using a valid passcode from a licensed amateur radio operator and used strictly by the servers to validate the connection to the server application.